O BEM E O MAL: UMA LEITURA EM GRANDE SERTÃO: VEREDAS - Gioppo, Fábio Ricardo (2014)
The novel Grande Sertão: veredas is the stage of numerous battles, but the principal fought battle that we can notice is the one Riobaldo locks with himself in seeking to unravel his condition of covenanting or not. Through philosophical concepts of Good and Evil developed by Baruch Spinoza (2013) and rhizome notion by Gilles Deleuze & Félix Guattari (1995), we will observe how Good and Evil movement unfolds itself in Riobaldo’s undertaken narratives along his greatest report. The work begins with the definitions from Good and Evil by Spinoza, and then to the establishment of the relations between these definitions and the rhizome’s guiding principles by Deleuze & Guattari. Thenceforth, we notice Riobaldian’s stories as a way to realize the difference lines’ dynamic operating in his reflections about Good and Evil in human’s actions. The devil in the whirlwind is the image which potentiates the comprehension that good can become evil, but evil also can become good; soon it is possible the perception that inside the backcountry there is no place just for hate exercises, betrayal and death, but also its reversal. Riobaldo’s narrative seems to us, therefore, like an ethic exercise that resumes his life and reflects it in the search for comprehension and redemption of himself in front of Good and Evil.